Study of distillation waste by clove for alternative fuel power plant: A review. Issue 1 (March 2021) - Sijabat, P Saragih; Siregar, Yulianta; Suherman,
Abstract: Today, fuel source energy is increasing demand in Indonesia, such as petroleum and coal. Fuel source energy is exhausted and cannot be renewed, therefore renewable energy is one solution for highly energy demand. Innovations of renewable energy like as biopellet from clove leaf refining waste is important for fuel power plant in Indonesia. This research is discuss about characteristics and quality of biopellet from clove leaf refining waste for alternative fuel in electricity generation. The clove leaf is dried up to moisture content from 15% to 30% then made of mesh size 20 and 40 with a milli hummer. then the clove leaf powder was mixed with glue or molasses with a ratio of 80% powder and 20% molasses then printed. Heated of temperature is 90°C, the second specimen is 110°C and the third specimen is 130°C, after it has reached the specified temperature the powder in the mold on the press or pressed with a pressure of 93 kg / cm 2 . The specimen have been printed and pressed for about 20 minutes. Biopellet can be an alternative fuel solution in Co-firing systems with coal that has been this is the main fuel for steam power generation.